New findings on CD16brightCD62Ldim neutrophil subtypes in sepsis-associated ARDS: an observational clinical study - Zhang, Jing; Gao, Chencheng; Zhu, Zhenxing; Li, Danyang; Qu, Lai; Xue, Qiuli; Wang, Guoqiang; Ji, Tong; Wang, Fang (Frontiers in Immunology, 2024)
Background: The CD16 bright CD62L dim neutrophil subtype is a recently identified neutrophil subtype. The aim of this study was to evaluate changes of peripheral blood CD16 bright CD62L dim neutrophils in patients with sepsis-associated ARDS.: We prospectively recruited adult patients with sepsis-associated ARDS in the intensive care unit (ICU). Patient demographic data, medical history information, and laboratory data were collected within 48 hours of enrollment, and flow cytometry was applied to analyze the CD16 bright CD62L dim neutrophil subtype in the patients' peripheral blood. Multifactor COX regression models were used to analyze factors affecting prognosis, and Spearman correlation coefficients were used to analyze clinical and laboratory indicators affecting complications of infection.Results: Of the 40 patients, 9 patients died by the 28-day follow-up, indicating a mortality rate of 22.5%. Patients in the nonsurvival group had higher CD16 bright CD62L dim neutrophil levels. Patients with sepsis-associated ARDS who had a baseline proportion of CD16 bright CD62L dim neutrophil subtypes to total neutrophils in peripheral blood >3.73% had significantly higher 28-day mortality, while patients with CD16 bright CD62L dim neutrophil subtypes counts >2.62×109/L were also associated with significantly higher 28-day mortality.The percentage of the CD16 bright CD62L dim neutrophil subtype (HR=5.305, 95% CI 1.986-14.165, p=0.001) and IL-8 (HR=3.852, 95% CI 1.561-9.508, p=0.003) were independent risk factors for the development of infectious complications in patients with sepsis-related ARDS.The percentage of CD16 bright CD62L dim neutrophil subtypes predicted an AUC of 0.806 (95% CI 0.147-0.964, P=0.003) for the development of infectious complications, and 0.742 (95% CI 0.589-0.895, P=0.029) for the prediction of death within 28 days.We identified for the first time that CD16 bright CD62L dim neutrophils are elevated in patients with sepsis-associated ARDS and are associated with infectious 3 complications and poor prognosis. The percentage of CD16 bright CD62L dim neutrophil subtypes may serve as a predictor of the development of infectious complications in patients with ARDS.